2021
DOI: 10.3348/kjr.2021.0212
|View full text |Cite
|
Sign up to set email alerts
|

Multidetector CT Characteristics of Fumarate Hydratase-Deficient Renal Cell Carcinoma and Papillary Type II Renal Cell Carcinoma

Abstract: Objective To investigate the multidetector computed tomography (MDCT) features of fumarate hydratase-deficient renal cell carcinoma (FH-deficient RCC) with germline or somatic mutations, and compare them with those of papillary type II RCC (pRCC type II). Materials and Methods A total of 24 patients (mean ± standard deviation, 40.4 ± 14.7 years) with pathologically confirmed FH-deficient RCC (15 with germline and 9 with somatic mutations) and 54 patients (58.6 ± 12.6 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
1
2
1
Order By: Relevance
“…This study analyzed the baseline characteristics, immunohistochemical features, gene mutation and prognosis of 16 FH-dRCC patients and compared with those of 44 patients with T2 pRCC. Many of our findings support the conclusions described in previous studies [ 14 , 18 ], including that FH-dRCC tend to present at a younger age than T2 pRCC (median age of 43.5 years), behave aggressively (50% of cases presented at tumor stage pT3a or higher) and more common in males. Lymph node and distant metastases were more frequent in FH-dRCC, as shown in the present study, metastases are commonly observed in the LNs, liver, lungs, bone and peritoneal seeding, and portend a poor prognosis.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This study analyzed the baseline characteristics, immunohistochemical features, gene mutation and prognosis of 16 FH-dRCC patients and compared with those of 44 patients with T2 pRCC. Many of our findings support the conclusions described in previous studies [ 14 , 18 ], including that FH-dRCC tend to present at a younger age than T2 pRCC (median age of 43.5 years), behave aggressively (50% of cases presented at tumor stage pT3a or higher) and more common in males. Lymph node and distant metastases were more frequent in FH-dRCC, as shown in the present study, metastases are commonly observed in the LNs, liver, lungs, bone and peritoneal seeding, and portend a poor prognosis.…”
Section: Discussionsupporting
confidence: 92%
“…As found in our study, the prognosis of FH-dRCC is worse than T2 pRCC. The proportion of patients with distant metastasis was higher in our study (81.3% vs. 13.6%) than in the study by Yang, while that of LNs metastasis was lower (37.5% vs. 6.8%) [ 18 ]. Since FH-dRCC is significantly more invasive than T2 pRCC, RN and lymph node dissection are recommended.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…Yang et al. ( 11 ) investigated the multidetector computed tomography (MDCT) features of FH-d RCC, and Nikolovski et al. ( 12 ) evaluated the imaging features of FH-d RCC on CT, MRI, and FDG PET.…”
Section: Discussionmentioning
confidence: 99%